Do cover crops give short term benefits for soil health? - Storr, Tom; Simmons, Robert W.; Hannam, Jacqueline A. (Association of Applied Biologists, 2018)
Cover crop use in the UK is increasing with establishment often before spring cereal crops. Therefore trials were implemented to assess two different cover crop mixtures for i) their ability to remediate soil compaction, ii) aid water management and iii) increase earthworm numbers. Two cover crop mixtures; frost sensitive (black oats, oil radish and mustard) and winter hardy (forage rye, oil radish and berseem clover) were compared to control plots. This replicated trial was based at G’s Growers on an organo-mineral soil with a cover crop sown between wheat harvested in August 2016 and maize sown in May 2017. The results suggest that in the short term there are small differences in soil physical characteristics. Notably at a depth of 10–20 cm there is a reduction in soil strength as measured by the penetrologger and shear vane following the frost sensitive cover crop mix. Juvenile earthworm population was significantly greater in the control treatment compared to the frost sensitive cover crop treatment. In May 2017 maize was established across all plots.
Keywords: Soil health; compaction; cover crops; frost sensitive; winter hardy